Wavelet transform for digital images watermarking - Khalifa, Othman Omran; Yusof, Yusnita (IIUM Press, 2011)
Internet evolution, along with the advancement of digital multimedia tools have create a major impact in making the storage and distribution of multimedia content a straightforward task. Issues on security have emerged and there is a vital need in protecting the digital content against counterfeiting, piracy and malicious manipulations. This paper describes the overview of digital watermarking technology, a relatively young research field considering that substantial interest began only in 1990's. Although history of watelmarking applications backdated from the use of paper watermarks in the 13th century, this technology has emerged as a promising field in digital context, motivated by security concerns that became acute with advances in computer technology and the development of the Web.